Pengujian Aktivitas Antioksidan Sediaan Stick Mask Ekstrak Etanol Daun Binahong (Anredera cordifolia (Ten.) Steenis): Aktivitas Antioksidan Sediaan Stick Mask Ekstrak Etanol Daun Binahong (Anredera cordifolia (Ten.) Steenis) - Selvia Maslamah Aan; Lina Rahmawati Rizkuloh; Srie Rezeki Nur Endah (Universitas Airlangga, 2025)
The development of the cosmetic industry created many new variations of cosmetic products. One of the beauty products that was developing was a stick mask with the benefit of preventing premature aging. Binahong (A. cordifolia) leaf was one of the plants that had antioxidant activity because of flavonoids that prevent premature aging of the skin. The study aimed to make a stick mask of ethanol extract of binahong (A. cordifolia) leaf and evaluation and test the antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method of the stick mask preparation. The preparation formulation was performed with variations in extract concentration at F0 0%, F1 25%, F2 30%, and F3 35%. Evaluation of the preparation includes organoleptic test, homogeneity, pH, spreadability, adhesives, dry time, and melting point test showed that the preparations met the standard requirements. The antioxidant activity of binahong (A. cordifolia) leaf ethanol extract stick mask in F3 with 35% extract concentration resulted in very strong antioxidant category with IC₅₀ 1,500 μg/mL. Keywords: Antioxidant, Binahong leaf (Anredera cordifolia (Ten.) Steenis), DPPH (2,2-diphenyl-1-picrylhydrazyl), Mask